Effect of plant growth regulators on fruit growth and quality development of syzygiumsamarangense (water apple/wax apple) / Adel Mohammed H Al-Saif - H Al-Saif, Adel Mohammed (2011)

(untitled)
The present study was conducted to investigate the effects of Gibberellic Acid (GA3), Naphthalene Acetic Acid (NAA) and N-2-chloro-4-pyridyl-N-phenylurea (CPPU) on the growth and quality development of water apple/ wax apple (Syzygium samarangense). GA3 at the concentrations of 0 (water control) 30, 60 and 90 ppm was used in experiment 1. NAA at the concentrations of 0 (water control), 6, 12 and 18 ppm was used in experiment 2. CPPU at the concentrations of 0 (water control) 10, 15 and 20 ppm was used in experiment 3. The swabbing technique of hormone application was used for all plant growth regulator applications in the three experiments. The growth regulators at different concentration levels (GA3, NAA and CPPU) were applied once a week starting from bud formation stage to flower opening stage (blooming), of twelve year old trees. In the GA3 experiments, it was observed that application of GA3 (30, 60 and 90 ppm) increased fruit length and diameter. Fruit length and diameter proved to be highest in GA3 at 60 ppm (60 mg/l). Furthermore, it increased the rate of fruit growth and maturity (represented by color) development in addition to increasing fruit number, weight and yield. Premature fruit drop was observed to have declined. With regard to fruit quality, the application of GA3 at 60 ppm increased the TSS , inverted sugar, fructose and total flavonoid content in wax apple. In addition, anthocyanin, potassium (K+) and total phenol content were higher in GA3 treated fruit than control fruit. From these experiments it can be concluded that swabbing 60 ppm (60 mg/l) of GA3 produced better performance in terms of size, yield and quality of wax apple fruit. In the NAA treated experiments, bud number was highest in 12 ppm NAA treated branch compared to other NAA treated and control branches. Bud drop decreased with decreasing NAA concentrations. Lowest fruit drop occurred in fruits treated with 12 ppm NAA. Fruit length and diameter were greatly enhanced at the ii different concentrations of NAA used. Yield and fruit weight had also significantly increased when 12 ppm NAA was used per branch. The chlorophyll content was also higher in 12 ppm NAA treated leaves than in control leaves. Dan similarity potassium and total flavonoid content, TSS, sucrose and fructose were also highest in 12 ppm NAA treated fruits. It was also observed that the anthocyanin content and pH value were highest in 12 ppm NAA. From this experiment it can be concluded that the swabbing application of 12 ppm (12 mg/l) NAA showed the best effects on fruit length, set, size and biochemical quality in wax apple fruits. In the CPPU treated experiments, higher bud drop was observed in 15 ppm CPPU than in the control fruit. Fruit length, diameter, per fruit weight and yield were observed to be higher in 15 ppm CPPU compared with the control. The highest increment in TSS content was recorded in 15 ppm CPPU treated-fruit. Similarity, the highest pH value was observed in 15 ppm CPPU treated fruits. Chlorophyll content was highest in 15 ppm CPPU treated-leaves. The results showed that the pH value, and the potassium content were higher in 15 ppm CPPU treated compared to those of the control fruit. The highest flavonoid, total phenolic and fructose content were recorded in 15 ppm CPPU concentration. Sucrose was also higher in 15 ppm CPPU than in other treatments. From this experiment it can be concluded that the swabbing application of 15 ppm (15 mg/l) CPPU showed the best effects on the fruit size and biochemical quality of the wax apple. Overall this study has shown that the plant growth regulators at different concentrations (60 ppm GA3, 12 ppm NAA and 15 ppm CPPU) applied using the swabbing technique greatly improved fruit growth and quality, when applied a week during bud initiation.